Multisystem Inflammatory Syndrome in Children in a 15-Year-Old Male with a Retropharyngeal Phlegmon - Paul Han; Jelena Douillard; Jerry Cheng; Anusha Ramanathan; David Tieu; Timothy Degner (Case Reports in Pediatrics)
This is a case of a 15-year-old male with an initial diagnosis of a retropharyngeal phlegmon who ultimately developed new symptoms and laboratory findings consistent with MIS-C. This case report demonstrates an atypical initial presentation for MIS-C that has not been reported in the literature.